1994
DOI: 10.1023/a:1018969506143
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An open, randomized, six-way crossover study was conducted in 12 healthy males to assess pharmacokinetics and bioinversion of ibuprofen enantiomers. The mean plasma terminal half-life (t1/2) of R(-)ibuprofen was 1.74 hr when intravenously infused as a racemic mixture and was 1.84 hr when intravenously infused alone. The mean t1/2 of S(+)ibuprofen was 1.77 hr when dosed as S(+)ibuprofen. Examination of values of both the absorption and disposition parameters of R(-)ibuprofen revealed that the kinetics of R(-)ib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The concentration of the nanoparticle suspension, which is usually 0.1% after preparation, can be increased up to 1% by rotary evaporation of water without changing the particle size and distribution. Concentrations from 0.1% to 1% should be sufficient because the described dextran-drug conjugates possess very high loading efficiencies and similar particle concentrations are used for pharmacokinetic studies and other nanoparticular systems [17,26]. For biological experiments, it is important to note that the nanoparticle suspensions based on dextran esters are stable under standard sterilizing procedures in an autoclave at 121°C and 2 bar for removing germs [6].…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…The concentration of the nanoparticle suspension, which is usually 0.1% after preparation, can be increased up to 1% by rotary evaporation of water without changing the particle size and distribution. Concentrations from 0.1% to 1% should be sufficient because the described dextran-drug conjugates possess very high loading efficiencies and similar particle concentrations are used for pharmacokinetic studies and other nanoparticular systems [17,26]. For biological experiments, it is important to note that the nanoparticle suspensions based on dextran esters are stable under standard sterilizing procedures in an autoclave at 121°C and 2 bar for removing germs [6].…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…2 The disposition properties of ibuprofen and fenoprofen are significantly different between enantiomers, [3][4][5] and these 2-APAs undergo the unidirectional chiral inversion from R-(-)-enantiomers to S-(+)-enantiomers in humans and animals. [6][7][8] It is reported that R-enantiomers are inverted to S-enantiomers exclusively in the rat liver, [9][10][11][12][13] though chiral inversion in the intestine is also suggested. 9,14 Recently, it was found that R-enantiomers have some pharmacological activities (analgesia).…”
Section: Introductionmentioning
confidence: 99%
“…17,18) Therefore, racemic ibuprofen at concentrations of 5, 10, 20, 40 and 80 mg/ml (corresponding to the concentration of R ibuprofen investigated) were coinubated with Caco-2 cells in the same condition as mentioned above to observe the effect of S-enantiomer on the inversion. The results were presented in Fig.…”
Section: Effect Of the Preexistence Of S-enantiomer On Inversion Prevmentioning
confidence: 99%